Compressive Strength, Splitting Tensile Strength, and Chloride Penetration Resistance of Concrete with Supplementary Cementitious Materials. Issue 4 (December 2020) - Mohamed, Osama; Hawat, Waddah Al; Najm, Omar
Abstract: This article presents the outcomes of a study that examined the durability and mechanical characteristics of self-consolidating concrete (SCC) mix in which a percentage of the required ordinary Portland cement (OPC) was substituted with either fly ash or ground granulated blast furnace slag (GGBS). The first part of the study evaluates the chloride penetration resistance and compressive strength of SCC mixes in which OPC in a designed control mix was partially replaced in a series of mixes by fly ash in percentages ranging from 10% to 40%. It noted that replacing OPC with fly ash at each of the four percentages studies improved chloride resistance of concrete compared to the control mix made of 100% OPC as binder. The 40% fly ash mix was the best performer in terms of resistance to chloride migration in contrast with the 100% OPC mix. Samples prepared using the 40% fly ash mix SCC mixes had the lowest compressive strength after 7 days of moist curing. However, the 28-day compressive strength of 40% fly ash mix was a healthy 55.75 MPa, only slightly lower than the 100% OPC mix. Tests also showed that adding 2% or fewer basalt fibres to the SCC mix in which 40% of OPC improves concrete resistance to chloride migration in contrast with the 40% fly ash mix that didn't contain basalt fibres. This paper also reports the relationship between splitting tensile strength and compressive strength of SCC mixes in which up to 80% of OPC was substituted with GGBS. A total of eight mixes were produced by varying the amounts of GGBS used to replace the OPC content of the control mix. The fresh properties were assessed through the flow test, visual stability index (VSI), and the T50. An empirical relationship was developed to predict the splitting tensile strength based on 28-day compressive strength, and its accuracy was evaluated in comparison to formulas in various design codes.